IMPLEMENTASI PEMBERIAN ASI EKSLUSIF TERHADAP PENAMBAHAN BERAT BADAN BAYI - Magdalena Limbong; Mohamad, Cindiyawati K.; Erna Kasim; Ekayanti Ahmad (Jurnal Kesehatan Panrita Husada, 2024)
Mother's milk (ASI) is a complex biological fluid that contains all the nutrients needed for the growth and development of the baby. Body weight is the result of an increase or decrease in all tissues in the body, including bone, muscle, fat, body fluids and others. Body weight is used as the best indicator to determine the state of nutrition and growth of the baby.This study aims to determine exclusive breastfeeding on infant weight gain.In this study the method used was interviews used to obtain information directly from respondents regarding matters relating to research and observation to collect case study data through secondary observations.Results:The results of this study indicate that there is weight gain before and after babies who are given exclusive breastfeeding.:can conclude that there is weight gain in Baby Ny. E before being given exclusive breastfeeding 2,640 g and after being given exclusive breastfeeding 2,830g while Baby Ny. A before being given exclusive breastfeeding it was 2,500 g and after being given exclusive breastfeeding it was 2,655 g so that it canbe concludedthat exclusive breastfeeding can increase the baby's weight significantly.Can add to the author's knowledge about the importance of exclusive breastfeeding and can be a reference for the future if you already have children.